“EFFECTIVE STRATEGIES FOR TEACHING ENGLISH VOCABULARY TO YOUNG LEARNERS IN UZBEKISTAN” (Лучшие интеллектуальные исследования, 2025)
As Uzbekistan strengthens its ties with the global community, proficiency in the English language has become a national priority. This focus begins with the youngest learners in the nation's primary schools. Moving beyond traditional rote memorization, educators are discovering that a dynamic, culturally-responsive approach is the key to successfully teaching English vocabulary. This article explores effective, evidence-based strategies tailored to the unique linguistic and cultural context of young Uzbek learners, advocating for a blend of global best practices and local integration.